Принципи формування атрактивності архітектурного середовища малих міст - Дида, Олександра Андріївна (Національний університет "Львівська політехніка", 2015)
Дисертація присвячена визначенню теоретичних основ та методики формування атрактивності архітектурного середовища малих міст. У теорію архітектури введено поняття архітектурної атрактивності як характеристики здатності об'єкта або середовища привертати увагу своїми візуально-змістовими властивостями. Зроблено класифікацію архітектурної атрактивності, визначено джерела її виникнення в умовах міста і ситуативні чинники, що впливають на напрям її розвитку. Сформульовано принципи і розроблено концепції формування атрактивності архітектурного середовища. Теоретичні основи дослідження і розроблену методику їх застосування апробовано на прикладі окремих контрольних малих міст Львівської області, що дало змогу підтвердити наукову гіпотезу дослідження. Диссертация посвящена определению теоретических основ и методики формирования атрактивности архитектурной среды малых городов. В теорию архитектуры введено понятие архитектурной атрактивности, характеризующей способность объекта или среды привлекать внимание своими визуально- содержательными качествами. Создана классификация архитектурной атрактивности, указаны источники ее возникновения, факторы, определяющие направление развития. Сформулированы принципы и разработаны концепции формирования атрактивности архитектурной среды. Теоретические основы исследования и разработанная методика их применения апробированы на примере отдельных контрольных малых городов Львовской области, что дало возможность подтвердить научную гипотезу исследования. The aim of this thesis is to determine the theoretical basis of forming of attractiveness of small towns' architectural space. Timeliness of the topic is based on the fact that an attractive architectural space attracts tourists and contributes to social and economic development of a small town. The concept of architectural attractiveness as a separate characteristic was explained and introduced into the theory of architecture as the ability of an object or environment to attract attention by its visual qualities. In comparison with Ukrainian equivalents, the proposed term "attractiveness" has a broader meaning. It derives from a Latin attraho which means to drag, to bring by force, and it may concern not only pleasant, but also negative characteristics of the environment. The research of architectural attractiveness was conducted on the basis of system approach. Taking into consideration the peculiarities of psychological perception of the environment and theoretical basis of architectural composition, the classification of architectural attractiveness was developed, and the new terminological apparatus for characteristics of different forms of its creation, existence, and influence for the recipient was proposed. It was also determined that the architectural attractiveness of an object arises from cooperation of visual meaningful parts. The architectural attractiveness of an object may be a result of emotionally positive, as well as emotionally negative peculiarities, and is a result of not only planned actions, but also spontaneous local architectural initiative. The potential sources of formation of architectural attractiveness in urban environment was determined. The factors influencing the direction and method of formation of architectural attractiveness of a small town were determined and classified. On the basis of this research, the main principles of formation of attractiveness of small towns' architectural space were theoretically proved and formed: "combination and correlation of visual and meaningful parts of architectural attractiveness"; "contrast of an attractant to the closest environment"; "preservation of general attractiveness of the system within individual attractiveness of an object"; "flexibility in choice of attractants". According to these principles, the concepts of formation of attractiveness of small towns' architectural space were developed. Due to the fact that the existence of architectural attractiveness is incompatible with the standard approach, the concepts were developed not for separate types of towns, but for relative situations arising subject to the presence of only one factor: location of a town in a region, its conceptual direction and the visual characteristics of an urban space. The concept of formation of attractiveness of real small towns' architectural space is a result of simultaneous use of several approaches chosen due to the factors existing in a given town. The theoretical results of the research, the principles were determined, the concepts of formation of attractiveness and methods of its practical use were developed and approved for controlled small towns of Lviv region. The situational conditions which make it possible to test all the variants of the developed concepts were also determined. The characteristics of general architectural attractiveness of a town within the system "region – country" were determined on the basis of data analysis of natural researches and sources concerning all the 74 small towns of the region. The perspective directions of formation of the individual architectural attractiveness of a small town within the system "small town – neighbouring small towns" were determined for six control objects. As a result, the individual concept of formation of attractiveness of a definite small town architectural space was proposed. Approbation makes it possible to give reasons for the proposed measures, to determine some peculiarities and priorities of their combined use, and to prove the hypothesis that the architectural attractiveness of a small town is formed through the interaction of conceptual and visual characteristics and its environment, on the basis of contrast to the neighbour towns. This applies only in case of preservation of common architectural peculiarities as a basis for formation of general architectural attractiveness of the region as a part of a bigger territorial system.
Принципы формирования атрактивности архитектурной среды малых городов
Principles for the creation of attractiveness of towns' architectural space
Keywords: архітектура; мале місто; атрактивність середовища; перспективний розвиток; архитектура; малый город; атрактивность среды; перспективное развитие; architecture; small town; attractiveness of environment; long-term development